Cubane Cross-Coupling and Cubane-Porphyrin Arrays - Senge, Mathias (My University, 2018)
Herein, an improved methodology for aryl‐cubane cross‐coupling is reported. The peculiarities of the cubane core and its behavior during cross‐coupling conditions were analyzed, while the versatility of this adapted Baran cross‐coupling methodology was demonstrated by the synthesis of various aryl‐cubane systems, including coupling products of cubanes and porphyrins. Furthermore, arm extension of alkynyl‐cubanes by Sonogashira reactions is demonstrated, showcasing the first proof of the stability of the cubane core in the presence of palladium catalysts.
PUBLISHED
Keywords: Cross-coupling; Cubanes; Nickel catalysis; Porphyrinoids; Sonogashira coupling